Knowledge Practices in Design: The Role of Visual Representations as `Epistemic Objects - Ewenstein, Boris; Whyte, Jennifer (Organization studies, 2009)
We use a detailed study of the knowledge work around visual representations to draw attention to the multidimensional nature of `objects'. Objects are variously described in the literatures as relatively stable or in flux; as abstract or concrete; and as used within or across practices. We clarify these dimensions, drawing on and extending the literature on boundary objects, and connecting it with work on epistemic and technical objects. In particular, we highlight the epistemic role of objects, using our observations of knowledge work on an architectural design project to show how, in this setting, visual representations are characterized by a `lack' or incompleteness that precipitates unfolding. The conceptual design of a building involves a wide range of technical, social and aesthetic forms of knowledge that need to be developed and aligned. We explore how visual representations are used, and how these are meaningful to different stakeholders, eliciting their distinct contributions. As the project evolves and the drawings change, new issues and needs for knowledge work arise. These objects have an `unfolding ontology' and are constantly in flux, rather than fully formed. We discuss the implications for wider understandings of objects in organizations and for how knowledge work is achieved in practice.